Loss of Nocturnin increases neuronal viability in oxidative stress conditions - Ojo, Anne E.; Olivas-Rasmussen, Crystal; Pappas, Samuel S.; Green, Carla B. (Frontiers in Neuroscience, 2025)
Oxidative stress, characterized by an imbalance between reactive oxygen species (ROS) and antioxidants, plays a critical role in neurodegenerative disorders like Parkinson’s Disease (PD) and is strongly associated with neuronal cell death. Nocturnin was identified as a NADP(H) phosphatase and key regulator of oxidative stress. NADPH serves as a crucial co-factor for enzymes which regenerate antioxidants, and downregulation of its levels increases sensitivity to oxidative stress mediated neurodegeneration. In this study, we examined how the loss of Nocturnin impacts redox homeostasis and neuronal survival in Cath.a-differentiated (CAD) cells and dopaminergic neurodegeneration in a mutant alpha-synuclein overexpression PD mouse model (DASYN53). Here we demonstrate that loss of Nocturnin increases CAD cell viability by increasing total glutathione levels, boosting metabolites involved in antioxidant defense, and reducing oxidative damage. Additionally, Nocturnin deletion in DASYN53 mice promotes midbrain dopaminergic neuron survival. These findings suggest that the loss of Nocturnin protects neurons from oxidative stress by increasing antioxidant defense, which rescues neurodegeneration of dopaminergic neurons.